anonymous
  • anonymous
\[y_P(x)=Ax^2+Bx+C\] \[y'_P=2Ax+B\] \[y''_P=2A\] \[ay''+by'+cy=Gx\] \[2A+(2Ax+B)-2(Ax^2+Bx+C)=x^2\] I understand all of the above except the \[...=x^2\] part. Why is G(x)=x^2?
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
across
  • across
You're just posting the particular solution to the ODE. Can you post the ODE itself so that we can give it a better look? I mean, you obtained some strange coefficients I didn't see until you decided to operate on the derivatives linearly.
anonymous
  • anonymous
oh I'm sorry I left one part out \[y''+y'-2y=x^2\] soo sorry....I guess I'm just tired, cant read my calc book =P
anonymous
  • anonymous
I have another question, which I'll probably figure out as soon as I post it :) I understand that: 2A=1 but why is: 2Ax+B=0 and Ax^2+Bx+C=0? should't they equal 1 as well?

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
@across
across
  • across
You're looking at the solution process incorrectly. Let \(y''+y'-2y=x^2\). Since this is an inhomogeneous ODE with source term \(x^2\), the particular solution is assumed to have the form \(y_p=Ax^2+Bx+C\). Differentiating as you did\[\begin{align}y_p'&=2Ax+B\\y_p''&=2A\end{align}\]and combining linearly yields\[\begin{align}(2A)+(2Ax+B)-2(Ax^2+Bx+C)&=x^2\\2A+2Ax+B-2Ax^2-2Bx-2C&=x^2\\(-2A)x^2+(2A-2B)x+(2A+B-2C)&=(1)x^2+(0)x+(0)\end{align}\]Observe that the \(-2A\) term on the LHS corresponds to the \(x^2\) on the RHS, while the \(2A-2B\) and \(2A+B-2C\) terms both correspond to \(0\). Hence, this implies that \(-2A=1\). I'm sure you can wrap the rest up from here.

Looking for something else?

Not the answer you are looking for? Search for more explanations.